Three decades of forest cover change in Uganda's Northern Albertine Rift Landscape. (December 2015) - Twongyirwe, Ronald; Bithell, Mike; Richards, Keith S.; Rees, W.G.
Highlights: We reconstruct forest cover patterns in the Northern Albertine Rift landscape. Measures of forest change at a larger-scale obscure more local patterns. Forest gains in Murchison Falls National Park offset losses in forest corridors. Protection of the gazetted forests in the last three decades is successful. Unprotected forests, on private landscapes suffer dramatic losses. Abstract: Deforestation within and outside protected areas is widespread in Western Uganda, but quantification of such forest changes is rare. In this study, spatio- temporal forest cover patterns in the Northern Albertine Rift Landscape were reconstructed for the period 1985–2014, over a range extending from Bugoma forest in the South of the region to as far as Murchison Falls National Park in the North, an area approximately 225 km North-South by 63 km East–West. We examine both the spatial and temporal heterogeneity of the land cover changes. Seven 30 × 30 m resolution, ortho-rectified, cloud-free Landsat images obtained from the USGS archive were analysed at the landscape- and three smaller scales. Forest classification using Landsat imagery appears robust; similar amounts are obtained from a UK-DMCii image (22 m resolution) taken a day before the Landsat scene in Dec, 2010. Our results show that larger-scale aggregate measures of total change can obscure more local patterns, in which protected areas and the national park maintain or grow forest cover, whilst the forest corridor areas that are not protected suffer drastic losses. Time-series show that the loss continues nearly linearly into the present around Bugoma, but seems to level off around Budongo Forest after 2010, apparently because almost all forested corridor areas have been cleared. At the landscape scale, between 1985 and 2014, the data suggest approximately 0.4% of initial cover was lost per year. However, this was mostly a result of the large protected forest blocks remaining relatively stable; deforestation was mostly situated in the corridor and riverine areas. Local-scale losses were most prominent in unprotected forests around Budongo and Bugoma, with annual losses at a much higher average rate about of 3.3% per year in each case. The annual rates of loss are higher than Uganda's average (1–3%). Forest cover in the protected zones expanded only marginally, with annual average increases of order 0.03% and 0.5% in Budongo and Bugoma reserves, respectively. Our results suggest that forest protection in the gazetted areas is successful, and the protection policy is working, but these forests are being isolated by large losses immediately outside the protected zones, in the forest corridors. This may have severe social and ecological consequences—both within and outside protected forests.